2017
DOI: 10.1007/s40820-017-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured ZnFe2O4/Fe2TiO5/TiO2 Composite Nanotube Arrays with an Improved Photocatalysis Degradation Efficiency Under Simulated Sunlight Irradiation

Abstract: To improve the visible light absorption and photocatalytic activity of titanium dioxide nanotube arrays (TONTAs), ZnFe2O4 (ZFO) nanocrystals were perfused into pristine TONTA pipelines using a novel bias voltage-assisted perfusion method. ZFO nanocrystals were well anchored on the inner walls of the pristine TONTAs when the ZFO suspensions (0.025 mg mL−1) were kept under a 60 V bias voltage for 1 h. After annealing at 750 °C for 2 h, the heterostructured ZFO/Fe2TiO5 (FTO)/TiO2 composite nanotube arrays were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…The subpeaks located at 711.7 and 726.1 eV are attributed to Fe 3+ . The subpeaks situated at 714.8 and 719.1 eV are contributions from the Fe 2+ and Fe 3+ satellite signals, respectively [ 12 ]. The intense peaks of the binding contribution of 711.7 and 726.1 eV demonstrated that Fe in the ZFO crystallites is mainly in a trivalent state.…”
Section: Resultsmentioning
confidence: 99%
“…The subpeaks located at 711.7 and 726.1 eV are attributed to Fe 3+ . The subpeaks situated at 714.8 and 719.1 eV are contributions from the Fe 2+ and Fe 3+ satellite signals, respectively [ 12 ]. The intense peaks of the binding contribution of 711.7 and 726.1 eV demonstrated that Fe in the ZFO crystallites is mainly in a trivalent state.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this spinel ferrite consists of non‐toxic, cheap and earth‐abundant elements, and is chemically stable in neutral and alkaline media . The photocatalytic properties of ZnFe 2 O 4 and its composites for the degradation of rhodamine B,, 4‐chlorophenol, methyl orange,, methylene blue, Acid Orange II,, and the reduction of Cr(VI) under UV or visible light irradiation have been investigated. Although ZnFe 2 O 4 has also been applied for PEC water splitting, most of the studies only use ZnFe 2 O 4 to modify the PEC performance of other photoelectrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Among the photocatalysts used for degradation of the diesel pollutant, the titanium dioxide (TiO 2 ) is widely selected on account of its superior reduction activity, good stability and inexpensive price. [12] TiO 2 photocatalyst can degrade many organic compounds in light, including the toluene, [13] trichloroethylene, [14] tetracycline, [15] methylene blue, [16] acetaminophen, [17] phenol [18] and bisphenol A. [19] On the other hand, TiO 2 also has some shortcomings, such as large band gap, low utilization of light energy.…”
Section: Introductionmentioning
confidence: 99%